A novel ex vivo model of compressive immature rib fractures at pathophysiological rates of loading. (November 2015) - Beadle, Nicola; Burnett, Timothy L.; Hoyland, Judith A.; Sherratt, Michael J.; Freemont, Anthony J.
Abstract: Introduction: Compressive rib fractures are considered to be indicative of non-accidental injury (NAI) in infants, which is a significant and growing issue worldwide. The diagnosis of NAI is often disputed in a legal setting, and as a consequence there is a need to model such injuries ex vivo in order to characterise the forces required to produce non-accidental rib fractures. However, current models are limited by type of sample, loading method and rate of loading. Here, we aimed to: i) develop a loading system for inducing compressive fractures in whole immature ribs that is more representative of the physiological conditions and mechanism of injury employed in NAI and ii) assess the influence of loading rate and rib geometry on the mechanical performance of the tissue. Methods: Porcine ribs (5–6 weeks of age) from 12 animals ( n =8 ribs/animal) were subjected to axial compressive load directed through the anterior–posterior rib axis at loading rates of 1, 30, 60 or 90 mm/s. Key mechanical parameters (including peak load, load and percentage deformation to failure and effective stiffness) were quantified from the load–displacement curves. Measurements of the rib length, thickness at midpoint, distance between anterior and posterior extremities, rib curvature and fracture location were determined from radiographs. Results: This loading method typically produced incomplete fractures around the midpoint of the ribs, with 87% failing in this manner; higher loads and less deformation were required for ribs to completely fracture through both cortices. Loading rate, within the range of 1–90 mm/s, did not significantly affect any key mechanical parameters of the ribs. Load–displacement curves displaying characteristic and quantifiable features were produced for 90% of the ribs tested, and multiple regression analyses indicate that, in addition to the geometrical variables, there are other factors such as the micro- and nano-structure that influence the measured mechanical data. Conclusions: A reproducible method of inducing fractures in a consistent location in immature porcine ribs has been successfully developed. Fracture appearance may be indicative of the amount of load and deformation that produced the fracture, which is an important finding for NAI, where knowledge of the aetiology of fractures is vital. Characteristic rib behaviour independent of loading rate and, to an extent, rib geometry has been demonstrated, allowing further investigation into how the complex micro- and nano-structure of immature ribs influences the mechanical performance under compressive load. This research will ultimately enable improved characterisation of the loading pattern involved in non-accidental rib fractures.